Transit Peptides From Photosynthesis-Related Proteins Mediate Import of a Marker Protein Into Different Plastid Types and Within Different Species - Eseverri, Álvaro; Baysal, Can; Medina, Vicente; Capell, Teresa; Christou, Paul; Rubio, Luis M.; Caro, Elena (Frontiers in Plant Science, 2020)
Nucleus-encoded plastid proteins are synthesized as precursors with N-terminal targeting signals called transit peptides (TPs), which mediate interactions with the translocon complexes at the outer (TOC) and inner (TIC) plastid membranes. These complexes exist in multiple isoforms in higher plants and show differential specificity and tissue abundance. While some show specificity for photosynthesis-related precursor proteins, others distinctly recognize non-photosynthetic and housekeeping precursor proteins. Here we used TPs from four Arabidopsis thaliana proteins, three related to photosynthesis (chlorophyll a/b binding protein, Rubisco activase) and photo-protection (tocopherol cyclase) and one involved in the assimilation of ammonium into amino-acids, and whose expression is most abundant in the root (ferredoxin dependent glutamate synthase 2), to determine whether they were able to mediate import of a nuclear-encoded marker protein into plastids of different tissues of a dicot and a monocot species. In A. thaliana, import and processing efficiency was high in all cases, while TP from the rice Rubisco small chain 1, drove very low import in Arabidopsis tissues. Noteworthy, our results show that Arabidopsis photosynthesis TPs also mediate plastid import in rice callus, and in leaf and root tissues with almost a 100% efficiency, providing new biotechnological tools for crop improvement strategies based on recombinant protein accumulation in plastids by the expression of nuclear-encoded transgenes.